Structural characterization of ANGPTL8 (betatrophin) with its interacting partner lipoprotein lipase. (April 2016) - Siddiqa, Amnah; Ahmad, Jamil; Ali, Amjad; Paracha, Rehan Zafar; Bibi, Zurah; Aslam, Babar
Abstract : Graphical abstract: Abstract : Highlights: Structural characterization of ANGPTL8 was performed. We used the computational strategy which includes sequence analysis, secondary structure prediction, comparative modeling and protein–protein interactions (PPI) analysis. The findings revealed that crystal structure of iSH2 domain of phosphatidylinositol 3-kinase(PI3K) ß subunit (PDB entry: 3mtt) as a suitable template for predicting the structure of ANGPTL8. ANGPTL8 is predicted to interfere with regulation of proteolysis, motility and localization of LPL besides steric block of its catalytic site. Abstract: Angiopoietin-like protein 8 (ANGPTL8) (also known as betatrophin) is a newly identified secretory protein with a potential role in autophagy, lipid metabolism and pancreatic beta-cell proliferation. Its structural characterization is required to enhance our current understanding of its mechanism of action which could help in identifying its receptor and/or other binding partners. Based on the physiological significance and necessity of exploring structural features of ANGPTL8, the present study is conducted with a specific aim to model the structure of ANGPTL8 and study its possible interactions with Lipoprotein Lipase (LPL). To the best of our knowledge, this is the first attempt to predict 3-dimensional (3D) structure of ANGPTL8. Three different approaches were used for modeling of ANGPTL8 including homology modeling, de-novo structure prediction and their amalgam which is then proceeded by structure verification using ERRATT, PROSA, Qmean and Ramachandran plot scores. The selected models of ANGPTL8 were further evaluated for protein–protein interaction (PPI) analysis with LPL using CPORT and HADDOCK server. Our results have shown that the crystal structure of iSH2 domain of Phosphatidylinositol 3-kinase (PI3K) p85 β subunit (PDB entry: 3mtt) is a good candidate for homology modeling of ANGPTL8. Analysis of inter-molecular interactions between the structure of ANGPTL8 and LPL revealed existence of several non-covalent interactions. The residues of LPL involved in these interactions belong from its lid region, thrombospondin (TSP) region and heparin binding site which is suggestive of a possible role of ANGPTL8 in regulating the proteolysis, motility and localization of LPL. Besides, the conserved residues of SE1 region of ANGPTL8 formed interactions with the residues around the hinge region of LPL. Overall, our results support a model of inhibition of LPL by ANGPTL8 through the steric block of its catalytic site which will be further explored using wet lab studies in future.